Acid-responsive HPMA copolymer-bradykinin conjugate enhances tumor-targeted delivery of nanomedicine - Appiah, Enoch; Nakamura, Hideaki; Pola, Robert; Grossmanová, Eliška; Lidický, Ondřej; Kuniyasu, Akihiko; Etrych, Tomáš; Haratake, Mamoru (Journal of controlled release, 2021)
Obstructed blood flow and erratic blood supply in the tumor region attenuate the distribution and accumulation of nanomedicines in the tumor. Therefore, improvement of these conditions is crucial for efficient drug delivery. In this study, we designed and synthesized a novel N-(2-hydroxypropyl)methacrylamide (HPMA)-based copolymer conjugate of BK, which possessed adequate systemic stability and tumor-selective action required to improve the accumulation of nanomedicines in the tumor. Levulinoyl-BK (Lev-BK) was conjugated to an HPMA-based polymer via an acid-cleavable hydrazone bond (P-BK). An acid-responsive release of Lev-BK from P-BK was observed, and P-BK alone after intradermal application showed below 10% of the BK activity, thus proving a reduction in the vascular permeability activity of BK when attached to the polymer carrier. P-BK pre-treatment improved blood flow in the tumor tissue by 1.4-1.7-fold, which was maintained for more than 4 h. In addition, P-BK pre-treatment increased the tumor accumulation of pegylated liposomal doxorubicin (PLD) by approximately 3-fold. Furthermore, P-BK pre-treatment led to superior antitumor activity of PLD and significantly improved the survival of tumor-bearing mice. The release of BK from P-BK in the acidic milieu of the tumor was a prerequisite for P-BK to exert its effect, as the vascular permeability enhancing activity of P-BK was negligible. Collectively, P-BK pre-treatment improved intratumoral blood flow and augmented tumor accumulation of nanomedicine, thereby resulting in a significant suppression of tumor growth. Therefore, these findings demonstrate that P-BK is a potential concomitant drug for improving the tumor delivery of nanomedicines.
Keywords: Animals; Doxorubicin; Nanomedicine; Methacrylates; bradykinin; Cell Line, Tumor; methakryláty; Neoplasms; nádory; Drug Carriers; Polymers; Antineoplastic Agents; Mice; protinádorové látky; Antitumor effect; myši; HPMA polymer; nanomedicína; doxorubicin; polymery; Bradykinin; nosiče léků; zvířata; EPR effect; nádorové buněčné linie